The Consumer Price Index - Hodgson, James (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1952)
SummaryA brief study of the new index called Consumer Price Index (C .P. I.) which will replace the Cost of Living Index (C. L. I.). In order to make such a change, specialists were called in to work on this for nearly three years. During the survey begun in 1948, the most modern methods of sampling were used. Instead of 1935-1939, the base period chosen was 1949. In view of the increasing importance of the index in the labour world, the author analyses briefly the changes made in the former index and emphasizes the problems involved in such a changeover.